2010
DOI: 10.1017/s0031182010000302
|View full text |Cite
|
Sign up to set email alerts
|

Parasite hybridization in African Macrogyrodactylus spp. (Monogenea, Platyhelminthes) signals historical host distribution

Abstract: Macrogyrodactylus spp. from the gills of Clarias gariepinus in Zimbabwe and Kenya, and C. anguillaris in Senegal were identified using haptoral sclerite morphology and by sequencing the nuclear ribosomal DNA internal transcribed spacers (ITS) 1 and 2, partial 18S and the complete 5.8S rRNA gene. A molecular phylogeny was constructed using all sequenced Macrogyrodactylus species to date. Based on morphology, Macrogyrodactylus congolensis, M. heterobranchii, M. clarii, and M. karibae were identified, with one sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 61 publications
5
47
0
Order By: Relevance
“…In most of these laboratory studies, hybrids showed reduced survival and impaired fertility already in the F1 or F2 generation. However, hybridization among parasites also occurs under natural conditions and was observed in monogeneans [29], schistosomes [30] and nematodes ( Anisakis ) [31]. The eggs isolated from the females from the present study were fixed in ethanol and therefore it could not be tested, if the hybrid larvae produced are viable, infective, and if they develop into fertile adults, but these issues will be investigated in further studies.…”
Section: Resultsmentioning
confidence: 99%
“…In most of these laboratory studies, hybrids showed reduced survival and impaired fertility already in the F1 or F2 generation. However, hybridization among parasites also occurs under natural conditions and was observed in monogeneans [29], schistosomes [30] and nematodes ( Anisakis ) [31]. The eggs isolated from the females from the present study were fixed in ethanol and therefore it could not be tested, if the hybrid larvae produced are viable, infective, and if they develop into fertile adults, but these issues will be investigated in further studies.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, additional molecular characterisation can also fruitfully assist in inferring the (common) phylogeographic history of host and parasite. This was exemplified in a study by Barson et al (2010) on Macrogyrodactylus Malmberg, 1957 of clariid catfishes, revealing ancient connections between presently distant host populations.…”
Section: Molecular Analysesmentioning
confidence: 90%
“…Another fruitful scientific approach can be catfish parasitology, certainly when applied to monogenean flatworm parasites, in view of their close relationship to their host species because of their one-host lifecycle and high host specificity. Indeed, research on Monogenea from catfish has proven useful both in disentangling monogenean speciation mechanisms (Pariselle et al 2003) and in reconstructing catfish biogeographical history (Barson et al 2010). Moreover, several monogenean genera have proven to be pathogenic to economically important cultured catfish.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they are strictly parasitic (i.e., adults cannot survive for a long time as free-living organisms), holoxenous (i.e., they have a direct lifecycle, with a short free-living larval stage which actively infests a new host), and generally oioxenous (i.e., parasite species are often species specific with regard to their host). A limited number of cases were made using these parasites, applying them in the fields of genetic population substructuring [68], historical patterns of their hosts' dispersal [69] or distribution [70], (co-)phylogenetic patterns [7173], and host identification [74]. …”
Section: Parasites As An Additional Source Of Informationmentioning
confidence: 99%